Peningkatan Hasil Belajar Matematika Siswa Kelas V SD Negeri 3 Nanggulan Melalui Penerapan Model Pembelajaran Kooperatif Tgt (Teams Games Tournaments) Tahun Ajaran 2022/2023 - Susilawati, Hani (Universitas Sebelas Maret, 2022)
This research aims to enhance the mathematics learning outcomes of fifth-grade students at SD Negeri 3 Nanggulan through the implementation of the cooperative learning model TGT (Teams Games Tournaments) in the academic year 2022/2023. The research method employed is classroom action research, consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. The subjects of this research are fifth-grade students at SD Negeri 3 Nanggulan. The results of the research indicate that the application of the cooperative learning model TGT effectively improves students' mathematics learning outcomes. There is a significant improvement in the understanding of concepts, problem-solving abilities, and active involvement of students in the learning process. Therefore, the TGT cooperative learning model can be an effective alternative to enhance the mathematics learning outcomes of students at the elementary school level.